ANALISIS HUBUNGAN ANTARA KEWARGANEGARAAN GLOBAL DAN BUDAYA KONSUMEN GLOBAL: PENGARUH MEDIASI KECERDASAN BUDAYA DAN MODERASI RELIGIUSITAS - Octavia Elvana Indra Putri Aluisi; Aluisius Hery Pratono; Firman Rosjadi Dj (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2019)
This study attempt to examine the complex relationship between global consumer culture and global citizenship by involving the mediating effect of cultural intelligence behavior and the moderating effect of religiosity. The structural equation model was developed to propose some hypothesis with support from previous literature. The empirical analysis involved online survey at the individual level, who voluntarily contributed to respond the survey. They represent young people, who represent various places in Indonesia. The results indicate that global consumer culture has a positive impact on global citizenship with mediating support from cultural intelligence behavior. In addition, the moderating effect of religiosity shows that the individual with high level of religiosity demonstrates high level of global citizenship. However, increasing level of global consumer culture for such individual has less impact on global citizenship than individual who has low level of religiosity. This study extends the discussion on global customer culture, which becomes a main concern to international business.